Precaution, Responsible Innovation and Beyond – In Search of a Sustainable Agricultural Biotechnology Policy - Bogner, Alexander; Torgersen, Helge (Frontiers in Plant Science, 2018)
The recent ruling by the European Court of Justice on gene edited plants highlighted regulatory inadequacy as well as a decades-old political problem, namely how to reconcile diverging expectations regarding agricultural biotechnology in Europe. Over time, regulators had tried out various tools to address concerns and overcome implementation obstacles. While initially focussing on risk (with the Precautionary Principle), they later tried to better embed technology in society (e.g. through Responsible Research and Innovation). The PP got criticised early-on; meanwhile, it seems to have lost much of its salience. RRI is associated with problems of participation and political impact, often rendering it a public awareness tool only. We discuss problems with both approaches and conclude that also RRI falls short of facilitating technology implementation in the way regulators might have had in mind. Rather than leaving political decisions to technical risk assessment or ethics and public awareness, we argue for re-establishing a broad yet sober process of opinion formation and informed decision-making in agricultural policy.